2010
DOI: 10.1016/j.ijfoodmicro.2010.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of lactic acid and lauricidin on spoilage organisms of chicken breast during storage at chilled temperature

Abstract: Different concentrations of lauricidin (LU, containing 1% lactic acid) and lactic acid alone (LA) were evaluated for their effectiveness in reducing naturally occurring microflora of raw chicken breasts. Chicken breasts were dipped in 0 (control), 0.5, 1.0, 1.5, and 2.0% solutions of LU (w/v) or LA (v/v) for 10, 20, and 30 min and stored at 4°C for 14 d. Total Plate Counts (TPC) and populations of Pseudomonas spp. and Enterobacteriaceae were determined before and after dipping and after storing for 1, 3, 7, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
6
8
0
Order By: Relevance
“…In the present work it was observed that washing with 1% or 2% lactic acid caused significant reductions (p < 0.05) in mesophilic, psychrotrophic, Pseudomonas, and Enterobacterales counts compared to untreated samples. These results agree with those reported by other authors as can be observed in Table 7 [28][29][30][31]. The differences found among the studies could be explained since longer treatments were applied by some authors (10 min instead of 5 min).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present work it was observed that washing with 1% or 2% lactic acid caused significant reductions (p < 0.05) in mesophilic, psychrotrophic, Pseudomonas, and Enterobacterales counts compared to untreated samples. These results agree with those reported by other authors as can be observed in Table 7 [28][29][30][31]. The differences found among the studies could be explained since longer treatments were applied by some authors (10 min instead of 5 min).…”
Section: Discussionsupporting
confidence: 92%
“…As Kolsarici and Candongan [28] we did not observe any adverse effect on sensory quality in chicken meat treated with 2% lactic acid. As in the present work Van der Marel et al [30] observed that lactic acid treatments caused a decline in the pH of the poultry meat depending on the lactic acid concentration used.…”
Section: Discussionsupporting
confidence: 67%
“…The sample meats were submitted to count for S. aureus 25 and TPC 26 according to standard procedures. The results were transformed to log CFU per gram of meat (log CFU/g).…”
Section: Microbiological Assaysmentioning
confidence: 99%
“…The production and consumption of chicken meat has rapidly increased in recent years (FAO, ), most likely due to its low price, high nutritional value, and sensory attributes (Anang, Rusul, Hooi Ling, & Bhat, ; Radha Krishnan et al, ). Stewed chicken, a traditional Chinese meat product, is considered a unique product in China, with exceptional flavor as a major contributor to consumer preference.…”
Section: Introductionmentioning
confidence: 99%